2022
DOI: 10.1002/anie.202200666
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Polyoxometalates: Selective Polyanion Binding and Ultrahigh Proton Conduction

Abstract: The rational development of an anion templation strategy for the construction of macrocycles has been historically limited to small anions, but large polyoxoanions can offer unmatched structural diversity and ample binding sites. Here we report the formation of a {Mo22Fe8} macrocycle by using the Preyssler anion, [NaP5W30O110]14− ({P5W30}), as a supramolecular template. The {Mo22Fe8} macrocycle displays selective anion binding behavior in solution. In the solid state, the 1 : 2 host–guest complex, {P5W30}2⊂{Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Great efforts have been dedicated to this mission, and numerous materials such as polyoxometalates [10,11], graphynes [12,13], recently developed porous materials [14][15][16][17], and so on have been constructed and studied thus far as proton-conductive electrolytes for application in PEM fuel cells. Among these functional materials, Nafion, a perfluorinated sulfonated polymer that shows an excellent proton conductivity and durability has gradually become a commercially accessible PEM electrolyte, although many issues in its fabrication and application still need to be overcome [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been dedicated to this mission, and numerous materials such as polyoxometalates [10,11], graphynes [12,13], recently developed porous materials [14][15][16][17], and so on have been constructed and studied thus far as proton-conductive electrolytes for application in PEM fuel cells. Among these functional materials, Nafion, a perfluorinated sulfonated polymer that shows an excellent proton conductivity and durability has gradually become a commercially accessible PEM electrolyte, although many issues in its fabrication and application still need to be overcome [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse materials, which include polyoxometalates, 10,11 graphynes, 12,13 and even recently developed porous materials, 14–17 have been synthesized and investigated as proton-conductive electrolytes so far. Among these functional materials, a perfluorinated sulfonated polymeric electrolyte, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of novel proton-conductive electrolytes is a fundamental important step in the process of commercializing PEM fuel cells. 7−9 Among the studied proton-conductive electrolytes such as graphynes, 10,11 polyoxometalates, 12,13 and some porous materials, 14−17 a perfluorinated sulfonated polymeric electrolyte, Nafion, has been employed as a PEM electrolyte because of its high proton conductivity and stability, although future large-scale practical utilization is still inhibited by its high cost, synthetic difficulties, and restricted working conditions. 18−20 Inspired by the success of Nafion, −SO 3 H functionalities have also been introduced into diverse materials and evaluated as Nafion alternatives to resolve the issues on the road to its largescale practical application.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the studied proton-conductive electrolytes such as graphynes, , polyoxometalates, , and some porous materials, a perfluorinated sulfonated polymeric electrolyte, Nafion, has been employed as a PEM electrolyte because of its high proton conductivity and stability, although future large-scale practical utilization is still inhibited by its high cost, synthetic difficulties, and restricted working conditions. Inspired by the success of Nafion, −SO 3 H functionalities have also been introduced into diverse materials and evaluated as Nafion alternatives to resolve the issues on the road to its large-scale practical application. Using the Cu­(I)-CAAC click reaction, we also grafted the −SO 3 H groups into a triazole-based porous organic polymer (TaPOP-1) during the in situ preparation process and a metal–organic framework entitled UiO-66 by the post-modification treatment, and investigations revealed that their proton conductivities were significantly increased in both the sulfonated TaPOP-1-SO 3 H and UiO-66-SO 3 H. , Despite the fact that numerous materials have been synthesized and studied for proton conduction, effective and economically affordable proton-conductive electrolytes are still urgently required for the large-scale application of PEM fuel cells in the upcoming “hydrogen economy” society.…”
Section: Introductionmentioning
confidence: 99%